1998
DOI: 10.1104/pp.117.3.821
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Promoter Activity for the Gene Encoding Pyruvate Orthophosphate Dikinase in Stably Transformed C4Flaveria Species1

Abstract: The C 4 enzyme pyruvate orthophosphate dikinase is encoded by a single gene, Pdk, in the C 4 plant Flaveria trinervia. This gene also encodes enzyme isoforms located in the chloroplast and in the cytosol that do not have a function in C 4 photosynthesis. Our goal is to identify cis-acting DNA sequences that regulate the expression of the gene that is active in the C 4 cycle. We fused 1.5 kb of a 5 flanking region from the Pdk gene, including the entire 5 untranslated region, to the uidA reporter gene and stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 40 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…It was proposed that the evolution of the C4 Flaveria chloroplastic PPDK isoform occurred through the acquisition of an alternative promoter region that directs high levels of mesophyllspecific expression of the gene (Monson 1999(Monson , 2003. Flaveria bidentis plants stably transformed with a construct encoding the 1.5 kb region flanking the 5′-end of the F. trinervia (C4) Pdk gene fused to the b-glucuronidase (GUS) reporter gene showed high levels of GUS expression in leaf mcs, lending support to the models (Rosche et al 1998).…”
Section: Molecular Evolution Of C4 Photosynthetic Enzymes In Flaveriamentioning
confidence: 83%
“…It was proposed that the evolution of the C4 Flaveria chloroplastic PPDK isoform occurred through the acquisition of an alternative promoter region that directs high levels of mesophyllspecific expression of the gene (Monson 1999(Monson , 2003. Flaveria bidentis plants stably transformed with a construct encoding the 1.5 kb region flanking the 5′-end of the F. trinervia (C4) Pdk gene fused to the b-glucuronidase (GUS) reporter gene showed high levels of GUS expression in leaf mcs, lending support to the models (Rosche et al 1998).…”
Section: Molecular Evolution Of C4 Photosynthetic Enzymes In Flaveriamentioning
confidence: 83%
“…In stable transformants of F. bidentis, the region −1212 to +279 from the transcriptional start site fused to uidA led to high levels of GUS in the M but lower amounts in the BS, stems, and roots (105). These data indicate that the FbPPDK promoter mainly drives expression in M but can also generate expression in BS cells (105).…”
Section: Pyruvate Orthophosphate Dikinasementioning
confidence: 88%
“…CA1 and CA3 precursor polypeptides were imported into isolated pea chloroplasts, and concomitant with import was processing of the CA1 and CA3 precursors to lower molecular mass polypeptides, which were protected from externally added protease. Work with other C 4 photosynthetic enzymes from C 3 and C 4 Flaveria species has shown that alterations in gene expression patterns occurred during the evolution of the C 4 forms of the enzymes, which have resulted in their increased levels of expression and celland organ-specific expression patterns (Marshall et al, 1996;Drincovich et al, 1998;Rosche et al, 1998;Lai et al, 2002;Gowik et al, 2004). Similar modifications are anticipated to have occurred during the evolution of the gene encoding the C 4 form of b-CA.…”
Section: F Pringlei Contains Two Chloroplastic B-casmentioning
confidence: 89%